Experience with Peroral Endoscopic Myotomy for Achalasia and Spastic Esophageal Motility Disorders at a Tertiary U.S. Center - Maen Masadeh; Peter Nau; Subhash Chandra; Jagpal Klair; John Keech; Kalpaj Parekh; Rami El Abiad; Henning Gerke (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Peroral endoscopic myotomy (POEM) is a novel procedure for the treatment of achalasia and spastic esophageal disorders. Experience with POEM is limited, but its reported outcomes are excellent. It is deemed safe even for patients with prior interventions. Methods This retrospective review included patients who underwent POEM at a tertiary US center. POEM was performed in a multidisciplinary approach by advanced endoscopists and foregut surgeons. Clinical success was defined as a post-POEM Eckardt score ≤3. Results A total of 125 patients were included. Median follow-up period was 18 months (interquartile range, 10-22 months). Clinical success was achieved in 92% of patients and persisted at 12 months in 88% of patients. Mucosal barrier failure (MBF) occurred in 7 patients, 2 of whom required surgical intervention. MBF was more common in patients with prior laparoscopic Heller myotomy (19% vs. 3%, p=0.015). MBF requiring surgical intervention occurred early in the learning curve. Conclusions POEM is safe and effective in the treatment of achalasia and spastic esophageal disorders even after failed prior interventions.